Short-Term Variability of Biological Production and CO2 System Around Dongsha Atoll of the Northern South China Sea: Impact of Topography-Flow Interaction - Tai, Jen-Hua; Chou, Wen-Chen; Hung, Chin-Chang; Wu, Kuan-Chieh; Chen, Ying-Hsuan; Chen, Tzong-Yueh; Gong, Gwo-Ching; Shiah, Fuh-Kwo; Chow, Chun Hoe (Frontiers in Marine Science, 2020)
The short-term variabilities in temperature, salinity, nitrate, chlorophyll a (Chl a), and carbonate chemistry data (i.e., pH, partial pressure of CO2 (pCO2), total alkalinity, and dissolved inorganic carbon) were concurrently investigated in the shallow (~50 m) and deep (~300 m) water areas around Dongsha Atoll of the northern South China Sea (NSCS). The results show that surface temperature and pCO2 were lower but that upward nitrate flux and Chl a were higher in the upper euphotic zone at the shallow-water area than those at the deep-water area. We suggest that the observed contrasting biogeochemical properties between the two areas could be attributed to the impact of topography-flow interaction. As tidal currents (or any other horizontal currents) interacted with the shallow topography, they may induce vertical isotherm displacements (e.g., internal tides/internal waves) that may enhance turbulent mixing, and thus can transport more nutrient-replete subsurface water into the euphotic zone and stimulate phytoplankton production. The stimulated biological production and the cooling effect induced by topography-flow interaction may collectively drive surface pCO2 down in the shallow water area. Though the present short-term hydrological and CO2 data, which to our knowledge were concurrently investigated for the first time in the NSCS, reveal that the topography-flow interaction could be a favorable mechanism for atmospheric CO2 uptake around Dongsha Atoll, more long-term observations are still needed to confirm that the similar processes can repetitively take place in topography-flow interaction prevalent areas.